Self-embedding robust digital watermarking algorithm with perfectly blind detection - Tian-yu YE (Tongxin xuebao)
Those existing robust watermarking algorithms couldn’t achieve perfectly blind detection.A robust watermarking algorithm with perfectly blind detection was proposed by introducing the self-embedding idea into robust watermarking literature.At first,the original image was split into non-overlapping blocks,and each block was transformed by DCT.The feature watermark was derived from judging the numerical relationship between each block’s DC coefficient and average of DC coefficients form all blocks.After encrypted by Logistic chaos sequence,the feature watermark was self-embedded into each block by adjusting two middle or low frequency DCT coefficients.Finally,the watermarked image was obtained after IDCT.The proposed algorithm achieved perfectly blind detection by combining self-embedding the encrypted feature watermark and blindly extracting authentication watermark.Experimental results show that the proposed algorithm has strong robustness to resist various attacks such as smoothing,adding noise,JPEG compression,resampling,cropping and geometric attacks like random row removal,downward shifting and right shifting.